Criminal psychology - Rowlands, David (Topics in applied psychology, 2024)
This carefully revised third edition of Criminal Psychology offers a vital, up-to-date account of the wide range of psychological contributions to the understanding of criminals and crime, its investigation, the legal processes of dealing with offenders, and helping victims